Perceptions of Thermal Comfort Felt by People in the Kalijodo Green Open Space - Mbarep, Daniel Putra Pardamean; Hasibuan, Hayati Sari; Moersidik, Setyo Sarwanto (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Kalijodo green open space has vegetated area 48 %. The ideal green open space, has vegetated area ​​80-90 % of total area. The results of the thermal comfort index in the Kalijodo green open space is 30.75. This condition makes the Kalijodo green open space in very uncomfortable status, and the thermal comfort index is categorized as comfortable is in 29 and below. This research was conducted to determine and analyze the perception of thermal comfort that  felt by the public in the green open space of Kalijodo. Descriptive analysis method is used to examine any information obtained from data processing from questionnaires filled out by 50 respondents. The results of this research on the perception of thermal comfort show that as many as 24 respondents felt very uncomfortable, 14 respondents felt comfortable, and 12 respondents felt uncomfortable when they were in the green open space of Kalijodo. These results indicate that the majority of people living in green open spaces are in line with the results of research on thermal comfort in the Kalijodo green open space which is in the very uncomfortable category. The condition of the Kalijodo green open space, which lacks vegetation, results in a very uncomfortable thermal comfort index value, so that the people there also feel the discomfort.